Approaches to the formation of an optimal personal investment portfolio in Ukraine - Сокровольська, Наталія Ярославівна; Гаватюк, Людмила Станіславівна; Карвацький, Максим Володимирович; Корбутяк, Аліна Георгіївна; Юрій, Едуард Олександрович (Investment management and financial innovations, 2021)
Globalization and IT progress are expanding the possibilities of using various financial instruments to create a personal investment portfolio. The purpose of the study is to differentiate the investment portfolio by the level of income of Ukrainian citizens and its impact on the effectiveness of personal finance management. Analysis of indicators of state and current investment trends allowed identifying the optimal ratio of profitability and risk in financial decisions of individuals by diversifying the investment portfolio, creating personal reserves, localizing investment instruments and minimizing the use of credit resources. The result of the study is the development and justification of criteria that an investor should meet during the investing. In particular, the formation of an individual investment portfolio depending on personal income allows everyone to justify an effective personal investment policy, taking into account the available investment tools. The paper covers the approaches to the formation of a person’s investment portfolio, depending on the level of his or her income. The paper also examines the need to form an optimal investment portfolio, depending on the real financial opportunities of a person.
Keywords: assets, capital, finance, financial decisions, investments, planning, risks, savings, Ukraine